2021
DOI: 10.1371/journal.pone.0260577
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Fos activation reveal that male and female rats differentially assess affective valence during CTA learning and expression

Abstract: Females are more affected by psychiatric illnesses including eating disorders, depression, and post-traumatic stress disorder than males. However, the neural mechanisms mediating these sex differences are poorly understood. Animal models can be useful in exploring such neural mechanisms. Conditioned taste aversion (CTA) is a behavioral task that assesses how animals process the competition between associated reinforcing and aversive stimuli in subsequent task performance, a process critical to healthy behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 171 publications
(227 reference statements)
1
2
0
Order By: Relevance
“…This suggested that males learned the negative association faster or were more sensitive to the negative effects of CRF activation. Interestingly, this mirrors findings from conditioned taste aversion studies where male rodents developed an aversion to lithium chloride-containing saccharin faster than females and were slower to extinguish this aversion [ 88 92 ].…”
Section: Discussionsupporting
confidence: 72%
“…This suggested that males learned the negative association faster or were more sensitive to the negative effects of CRF activation. Interestingly, this mirrors findings from conditioned taste aversion studies where male rodents developed an aversion to lithium chloride-containing saccharin faster than females and were slower to extinguish this aversion [ 88 92 ].…”
Section: Discussionsupporting
confidence: 72%
“…Like in mice, female rats emit more 50 kHz calls when sexually receptive (Thomas and Barfield, 1985 ; Matochik and Barfield, 1994 ; Bernanke et al, 2021 ; Lenell and Johnson, 2021 ) and males increase their calling rate in the presence of a receptive female (McGinnis and Vakulenko, 2003 ; Portfors, 2007 ) indicating the potential of USVs to modulate female mate choice. However, there has been controversy regarding the importance of male calls in female mate choice; while some studies support the importance of male calls (Thomas and Barfield, 1985 ; Gerson et al, 2019 ) eliciting female approach behavior (Seffer et al, 2014 ; Willadsen et al, 2014 ; Berg et al, 2018 , 2021 ; Kisko et al, 2018 , 2020 ), others found that females choose vocalizing vs. non-vocalizing males equally often (Snoeren et al, 2014 ).…”
Section: Contribution Of Ultrasonic Vocalizations To the Evaluation A...mentioning
confidence: 99%
“…Our object recognition results clearly indicate a sex-dependent effect of stimulation of TMN HA neurons on memory. Sex differences in cognitive functions have been documented in humans 30 and experimental animals 31,32 . For instance, robust sexual dimorphism was also described in the recruitment of circuits underlying fear memory and in the evolution of whole-brain networks over time 33 .…”
Section: Discussionmentioning
confidence: 99%